2003
DOI: 10.1046/j.1475-1313.2003.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors in teenage high school students in Singapore

Abstract: We aimed to study the prevalence of refractive conditions in Singapore teenagers. Grade 9 and 10 students (n = 946) aged 15–19 years from two secondary schools in Singapore were recruited. The refractive errors of the students’ eyes were measured using non‐cycloplegic autorefraction. Sociodemographic data and information on risk factors for myopia (such as reading and writing) were also obtained using an interviewer‐administered questionnaire. The prevalence of refractive conditions was found to be: myopia [sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(125 citation statements)
references
References 31 publications
(64 reference statements)
13
108
2
1
Order By: Relevance
“…Comparable study by Waziri-Erameh and Omoti [34][35][36][37][38][39] reported similar findings with majority of patients (70.18%) with visual acuity better than 6/18, 25.49% with visual acuity between 6/60-6/18 while 4.33% had visual acuity worse than 6/60. However, one study by Hassan et al [40][41][42][43][44][45] reported higher percentage of patients with visual acuity between 6/60-6/18 (46.34%) followed by visual acuity better than 6/18 (39.84%) and then visual acuity worse than 6/60 (13.82%). The higher case of satisfactory visual acuity (better than 6/18) could be a reason for the low prevalence of refractive error in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable study by Waziri-Erameh and Omoti [34][35][36][37][38][39] reported similar findings with majority of patients (70.18%) with visual acuity better than 6/18, 25.49% with visual acuity between 6/60-6/18 while 4.33% had visual acuity worse than 6/60. However, one study by Hassan et al [40][41][42][43][44][45] reported higher percentage of patients with visual acuity between 6/60-6/18 (46.34%) followed by visual acuity better than 6/18 (39.84%) and then visual acuity worse than 6/60 (13.82%). The higher case of satisfactory visual acuity (better than 6/18) could be a reason for the low prevalence of refractive error in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A trend for increasing anisometropia with age is also supported by studies of Bourne and colleagues 25 and Quek and associates. 26 The reason for the development of anisometropia in some adult eyes is unclear, but Almeder and colleagues have suggested that much anisometropia observed in adults is actually not the cause, but instead may be the result, of preexisting amblyopia. 21 It therefore appears that prevalence data from adults should not be extrapolated to children.…”
Section: Prevalence Of Anisometropia Anisometropic Amblyopia and Thmentioning
confidence: 99%
“…1 Its public health costs can be considerable, most obviously from direct costs of refractive correction arising from purchases of spectacles, contact lenses, and their accessories. Globally, myopia cost US$4.6 billion in 1990.…”
Section: Introductionmentioning
confidence: 99%